Perbandingan Studi Perbandingan Kewenangan Penyidikan Pidana Berdasarkan Sistem Peradilan Indonesia dan Singapura: Abstrak, Pendahuluan, Metode Penelitian, Hasil Penelitian dan pembahasan, kesimpulan dan daftar pustaka - Elen Oktaviani; Abdul Fickar Hadjar (Faculty of Law, Universitas Trisakti, 2023)
Investigation is a substantial first step in the law enforcement process. Indonesia and Singapore apply different legal systems to reform criminal procedural law need to be carried out through comparative studies. The problem formulation is what are the similarities and differences in criminal investigation authority based on the Indonesian and Singaporean legal systems. The research method was carried out normatively with the nature of the research using analytical descriptiveness, the type of data used was secondary data, qualitative data analysis and conclusions were drawn based on the deductive logic method. The results of the research and discussion are that investigations in Indonesia are regulated in the Criminal Procedure Code, while in Singapore they are regulated in the 2010 Criminal Procedure Code, there are exceptions regarding special criminal regulations. In conclusion, the same investigative authority is carried out by the police, there are exceptions regarding the investigation of special criminal acts where the investigator is from the relevant agency even though the police are also the investigator, differences in the legal systems used by the two countries, differences regarding the time to be accompanied by a lawyer, and there are differences time period submission of case files to the prosecutor's office.